(untitled) (Journal of Parents and Teachers, 2014)
Family breakdown, an aspect that is increasingly frequent and common in our society, not only entails implications for the members of the couple, but also affects, fundamentally, the children. It is therefore important that parents find a space of neutral dialogue in which to meet and not break, with it, the dynamics of children, in an aggressive manner. This article explains what is the Family Encounter Point of the Fonseca Center, an initiative of the Society of Jesus together with the Department of Family and Promotion of Employment, Women and Youth.